Target Stealth - Merek, Jack (New York Warner Books, 1989)
Documents detailing the operating capacity of the nuclear B-2 "Stealth Bomber" have been snatched from a Russian agent in Beirut. As the White House tries to locate the leak, the chief of Iranian Intelligence is planning to hijack the bomber and threaten the world with nuclear parity.
Keywords: a